A polypyrrole/anthraquinone-2,6-disulphonic disodium salt (PPy/AQDS)-modified anode to improve performance of microbial fuel cells - Feng, Chunhua; Ma, Le; Li, Fangbai; Mai, Hongjian; Lang, Xuemei; Fan, Shuanshi (Biosensors & bioelectronics, 2010)
This study reports a new approach of improving performance of microbial fuel cells (MFCs) by using a polypyrrole/anthraquinone-2,6-disulphonic disodium salt (PPy/AQDS)-modified anode. The immobilization of AQDS on a carbon felt anode was accomplished by electropolymerization of pyrrole while using AQDS as the dopant. The dual-chamber MFC operated with this modified anode in the presence of Shewanella decolorationis S12 showed the maximum power density of 1303 mW m −2, which was 13 times larger than that obtained from the MFC equipped with an unmodified anode. Evidence from cyclic voltammerty (CV) and scanning electron microscopy (SEM) results indicated that the increase in power generation was assigned to the increased surface area of anode, the enhanced electron-transfer efficiency from the bacteria to the anode via immobilized AQDS, and an increase in the number of bacteria attached to anode.